EFFECT OF THE FREQUENCY OF PROBIOTIC USE ON THE PRODUCTIVITY AND INCUBATION PROPERTIES OF EGGS OF THE MEAT PRODUCTION DIRECTION - Ovchinnikov; Matrosova; Ovchinnikova; Yermolova; Konovalov (Revista Inclusiones, 2020)
The use of probiotics Levisel SB Plus and Cellobacterin-T in the amount of 0.50 kg/t of mixed fodder in the diet of young herd replacement of the meat direction during the growing period from 3 to 45 days allowed to get homogeneity by 20.9 and 13.1 % above the analogues of the control group. Probiotic feed additive Levisel SB Plus increased the number of fertilized eggs by 1.96 %, hatchability – by 0.90 %, hatchery waste decreased by 2.7 %, feed costs decreased by 9.6 %. However, the best production results were shown by the group with a similar rate of probiotic Cellobacterin-T introduction, which had these indicators, respectively, of 2.0 %, 1.28, 4.2 and 10.4%.